Fire safety training for workers: an investigation into how learning modalities in VR relate to performance and self-evaluations - Muffato, Veronica; Mazzella di Bosco, Marta; Zuzzi, Sara; Pellegrini, Daniela; Meneghetti, Chiara (Frontiers in Psychology, 2026)
Learning to handle emergency situations is a fundamental goal of safety training. Virtual Reality (VR) is increasingly used to support procedural learning, yet evidence on learning conditions and learners’ perceptions is still limited in workplace fire safety training. In Study 1a, we investigated whether various active VR learning formats are more effective than traditional methods (passive video with verbal explanations) for teaching fire safety procedures (Aim 1) and examined how these methods relate to participants’ self-assessment of the experience (Aim 2). A total of 111 participants (78 females, aged 20–28) were assigned to three learning groups: (a) video-slide learning, (b) basic VR with avatar instructions, and (c) dual-mode (VR with avatar instructions plus panel information). All participants were then tested in a VR fire scenario and self-assessed their cognitive load, immersiveness, presence, motivation, and perceived stress. The results showed that both VR groups outperformed the video-slide learning group in execution time and total score, while only the basic VR group showed fewer errors than the video-slide learning group. Participants reported low cognitive load and high immersiveness, presence, and motivation with the VR experience. However, high levels of perceived stress during the simulation were associated with lower performance, confirming the negative effects of stress on learning. In Study 1b, we aimed to compare workers (N = 16, 9 females, 25–60 years old) with students to verify the results in a realistic context, using only the dual-mode VR learning condition. The results show no significant differences between the nonworker sample and the worker sample, suggesting that the selected procedure is applicable in a professional context. Overall, these results suggest that well-designed active VR training can enhance procedural safety learning and that psychological dimensions should be considered in its design and implementation.